Hubungan perilaku caring perawat dengan tingkat kecemasan keluarga pasien selama menunggu perawatan di instalasi gawat darurat - Dara, Indika Dwi; Faozi, Ekan (Holistik Jurnal Kesehatan, 2025)
Background: Swift and precise healthcare is crucial for emergency patients in the ER. The anxiety experienced by patients' families often hinders the healing process. Factors contributing to this anxiety include emotional pressure and the inadequate attitudes of healthcare personnel towards families. Therefore, nurses must provide professional care, one aspect of which is caring behavior. Purpose: To determine the relationship between nurses' caring behavior and the level of anxiety experienced by patient families while waiting for treatment in the emergency room. Method: Correlational quantitative research with a cross-sectional approach. The sample in this study amounted to 99 respondents of patient families at the Emergency department, Ir. Soekarno Sukoharjo.  regional hospital. The study was conducted in October-November 2024. Univariate data analysis used the frequency analysis test and bivariate data Spearman correlation test. Results: Respondents who assessed the caring behavior of nurses in the good category in a state of not experiencing anxiety amounted to 33 respondents (80.5%), while respondents who assessed the caring behavior of nurses in the sufficient category in a state of not experiencing anxiety amounted to 8 respondents (19.5%) and respondents There was 1 respondent (9.1%) who rated nurses' caring behavior as poor in a situation of experiencing severe anxiety. The Spearman statistical test results obtained a p value of 0.001 (<0.05). Conclusion: There is a significant relationship between nurses' caring behavior and the patient's family's level of anxiety while waiting for treatment in the emergency room. Suggestion: Future research can carry out research by adding other factors that can influence nurses' caring behavior and also family anxiety when in the emergency room.   Keywords: Anxiety; Caring; Emergency Department; Family; Nurse.   Pendahuluan: Pelayanan kesehatan yang cepat dan tepat sangat penting bagi pasien gawat darurat di IGD. Kecemasan yang dialami keluarga pasien sering menghambat proses penyembuhan. Faktor-faktor penyebab kecemasan ini meliputi tekanan emosi dan juga bisa timbul karena sikap petugas kesehatan yang kurang terhadap keluarga. Oleh karena itu, perawat harus memberikan pelayanan profesional salah satunya perilaku caring. Tujuan: Untuk mengetahui hubungan antara perilaku caring perawat dan tingkat kecemasan yang dialami oleh keluarga pasien saat menunggu perawatan di instalasi gawat darurat (IGD). Metode: Penelitian kuantitatif korelasional dengan pendekatan cross sectional. Sampel pada penelitian ini berjumlah 99 responden keluarga pasien di Instalasi Gawat Darurat RSUD Ir.Soekarno Sukoharjo. Penelitian dilakukan pada Oktober-November 2024. Analisis data univariat menggunakan uji analisis frekuensi dan data bivariat uji korelasi Spearman. Hasil: Responden yang menilai perilaku caring perawat dengan kategori baik dalam keadaan tidak mengalami kecemasan berjumlah 33 responden (80.5%), sedangkan responden yang menilai perilaku caring perawat dengan kategori cukup dalam keadaan tidak mengalami  kecemasan berjumlah 8 responden (19.5%) dan responden yang menilai perilaku caring perawat dengan kategori buruk dalam keadaan mengalami kecemasan berat berjumlah 1 responden (9.1%). Hasil uji statistik Spearman diperoleh nilai p 0.001 (<0.05). Simpulan: Adanya hubungan yang signifikan antara perilaku caring perawat dengan tingkat kecemasan keluarga pasien selama menunggu perawatan  di Instalasi Gawat Darurat. Saran: Penelitian selanjutnya dapat melakukan penelitian dengan menambahkan faktor-faktor lain yang dapat memengaruhi perilaku caring perawat dan juga kecemasan keluarga saat di IGD.   Kata Kunci: Caring; Perawat; Instalasi Gawat Darurat; Kecemasan; Keluarga.